Capabilities of «motion capture» systems in identifying features of cyclists pedaling techniques - Sushchenko V.P.; Lukashevich D.A.; Guseynov D.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determination of kinematic parameters characterizing pedaling technique using «motion capture» systems. Methods and structure of the study. To solve this problem, a pilot study was organized with the participation of 2 athletes who had experience competing at major international cycling competitions. Each athlete performed a test with a progressive increase in power to failure on a bicycle ergometer using a Cyclus 2 bicycle station and a Simi Aktisys motion capture system. Results and conclusions. Analysis of the obtained video sequences after their computer processing made it possible to identify the most variable biokinematic links in the dynamics of performing a test on a bicycle ergometer with a linearly increasing load (15 W/min). The most pronounced changes were observed for the ankle joint and the position of the torso relative to the horizontal. The results obtained allow us to draw logical conclusions about the possibility of using «motion capture» systems to obtain accurate data characterizing the features of the kinematic parameters of pedaling, without affecting the biomechanical structure of the athlete’s movements. The use of new approaches in the study of kinematic characteristics of pedaling will improve the efficiency of monitoring the technical readiness of highly qualified cyclists.